Cancellation Of The Hajj: Analysis Of Islamic Law, Regulations, History, Ta'limatul Hajj And Its Impact On The Social And Spiritual Aspects Of Society - Endang Jumali (Jurnal IUS Kajian Hukum dan Keadilan, 2020)
The Covid-19 pandemic has had a tremendous impact not only on the economic aspect but also on the Hajj implementation cancellation in 2020. The purpose of this article is to analyze the cancellation of the Hajj from the perspective of analysis of Islamic law, regulations, history, talimatul Hajj, and its impact on the social and spiritual aspects of society. The method used in this article is a qualitative research method with a library research approach. This article concludes that two fundamental aspects of Islamic Law justify the decision to cancel the Hajj: first, from the element of maqashid al-sharia, namely the safety of the human soul as from protecting the soul (hifzh al-nafs), second from the aspect of fiqh, the requirements compulsory Hajj, namely being able (istitha'ah) in the course of the pilgrimage has not been fulfilled. From the regulatory element, in article 41 of Law Number 8 of 2019, the Minister of Religion is responsible for protecting pilgrims and pilgrim officers before, during, and after Hajj pilgrims and pilgrim officers carry out the pilgrimage. From a historical aspect, the expedition was canceled several times because of war and pandemic diseases. Then from the element of the talimul Hajj of Saudi Arabia, all the congregation can't do it because of the Covid-19 pandemic. In the social and spiritual aspects, the pilgrimage is a combination of soul, wealth and social. While performing the Hajj, someone is performing a soul-training ritual.